Perencanaan Strategis Pendidikan Islam di SMP Islam Terpadu Jamanis Parigi Kabupaten Pangandaran: Pengabdian - Baharuddin; Muthi, Ibnu; Muntaha; Yuli Sugiarti, Diyah; Apriliantoni; Hasby Assidiqi, Muhammad; Sabeni; Dzul Azmi, Muhammad; Elishabat Ishomuddin, Lisa; Nadia Laila, Siti; Fadllillah, Nurul; Suherman, Ujang; Alfi Rahmani, Rochayah; Haryati, Nurlaela; Fajarwati, Desi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The rapid advancement of technology presents both challenges and opportunities for Islamic education, such as the separation of religious and general knowledge, weak research culture, unstable curriculum, limited human resources, and suboptimal management. This community service aimed to enhance understanding of the importance of strategic planning in improving educational quality at SMP Terpadu Jamanis Parigi, Pangandaran. The implementation method combined observation, descriptive approach, FGD, and active participation using a persuasive-educative approach. Observation was used to map the actual management conditions, while active participation involved all school stakeholders. Results showed 80% of participants experienced significant improvement in understanding and skills, and the remaining 20% showed moderate improvement, demonstrating the effectiveness of the solutions provided. The impact includes the development of an actionable plan to improve education quality, potential for further training in financial management and adaptive curriculum development, as well as independent learning modules, group-based learning, and online discussion forums. The program highlights strategic planning as a crucial guide for educational institutions in achieving their vision and mission.